Nitroreductase-triggered activation of a novel caged fluorescent probe obtained from methylene blue1. Issue 64 (18th August 2015) - Bae, Jungeun; McNamara, Louis E.; Nael, Manal A.; Mahdi, Fakhri; Doerksen, Robert J.; Bidwell, Gene L.; Hammer, Nathan I.; Jo, Seongbong
<x xml:space="preserve">Abstract</x> A new fluorescent probe caged with a p-nitrobenzyl redox switch enables selective switching on of fluorescence by nitroreductase.